2004
DOI: 10.1038/sj.bjp.0705718
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of a novel dihydropyridine K+ channel opener, A‐312110, with recombinant sulphonylurea receptors and KATP channels: comparison with the cyanoguanidine P1075

Abstract: 1 ATP-sensitive K þ channels (K ATP channels) are composed of pore-forming subunits (Kir6.x) and of regulatory subunits, the sulphonylurea receptors (SURx). Synthetic openers of K ATP channels form a chemically heterogeneous class of compounds that are of interest in several therapeutic areas. We have investigated the interaction of a novel dihydropyridine opener, A-312110 ((9R)-9-(4-fluoro-3-iodophenyl)-2,3,5,9-tetrahydro-4H-pyrano [3,4-b]thieno [2,3-e]pyridin-8(7H)-one-1,1-dioxide), with SURs and Kir6/SUR ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…A KCO P-1075 binds with high affinity to cardiac KATP channel but not to pancreatic β-cell KATP channel [56,57]. We demonstrated that the selective mitoKATP These data demonstrated the fundamental possibility of creating the cardioselective mitoKATP channel opener without negative hemodynamic and proarrhythmic effects.…”
Section: Katp Channel Blockersmentioning
confidence: 86%
See 1 more Smart Citation
“…A KCO P-1075 binds with high affinity to cardiac KATP channel but not to pancreatic β-cell KATP channel [56,57]. We demonstrated that the selective mitoKATP These data demonstrated the fundamental possibility of creating the cardioselective mitoKATP channel opener without negative hemodynamic and proarrhythmic effects.…”
Section: Katp Channel Blockersmentioning
confidence: 86%
“…KCOs are categorized as follows for their ability to induce relaxation of coronary arteries: rilmakalim > P1075 > bimakalim > > levcromakalim > aprikalim > minoxidil > (−)‐pinacidil > (+)‐pinacidil > nicorandil > diazoxide [18]. A KCO P‐1075 binds with high affinity to cardiac KATP channel but not to pancreatic β‐cell KATP channel [56, 57]. We demonstrated that the selective mitoKATP channel opener BMS‐191095 reduced infarct size in dogs with CAO (90 min) and reperfusion (5 h) without effects on hemodynamics [58].…”
Section: The Regulation Of Katp Channels By Katp Inhibitors and Katp ...mentioning
confidence: 99%
“…Owing to high nonspecific binding, [ 3 H]GBC binding experiments were not possible in the presence of MgATP nor in intact cells. The K D value determined here for P1075 binding to SUR2A in the presence of MgATP (Table 3) is the same as that determined earlier (Hambrock et al ., 1999) and is 2–5 times lower than that of SUR2B (Hambrock et al ., 1999; Felsch et al ., 2004). The mutation Y1206S increased the affinity of SUR2A for GBC ∼5 times (Table 1) and enhanced the potency of GBC to inhibit [ 3 H]P1075 binding ∼4 × (Table 3) but it did not affect the affinity of SUR2A for openers (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, compounds such as the tertiary carbinol ZD6169 and aryl squarate WAY 133537 with modestly improved in vivo selectivity for the urinary bladder relative to benzopyrans such as cromakalim and celikalim have emerged ( Howe et al ., 1995 ; Wojdan et al ., 1999 ). More recently, compounds belonging to the 1.4‐dihydropyridine class including A‐312110 and A‐278637 have been synthesized and characterized ( Gopalakrishnan et al ., 2002 ; Davis‐Taber et al ., 2003 , Felsch et al ., 2004 ). In particular, A‐278637 was demonstrated to possess enhanced potencies for suppression of unstable bladder contractions vs mean arterial blood pressure effects in an obstructed pig model relative to earlier generation compounds ( Brune et al ., 2002 ).…”
Section: Introductionmentioning
confidence: 99%